Ecologia de comunidades zooplanctônicas em lagoas associadas a veredas no município de Uberlândia, MG - Pinese, Olívia Penatti (2008)
Ponds of veredas, a palm swamp environment associated with headwaters, appears among the most important continental aquatic habitats on the planet. In these ponds, banks of macrophytes occurs with frequency, maintaining the aquatic productivity and the increase of habitat heterogeneity, thereby generating great biological diversity in their environment. One of the main communities founded in these ecosystems are the zooplankton, a group of animals that play an important role in the transference of primary productivity to consumers of higher trophic levels. The aim of this study were to determine and compare the composition of zooplankton Copepoda, Cladocera and Rotifera in two lagoons associated with the vereda palm swamp, that differs on the presence/absence of aquatic macrophytes in the body water. The ponds are situated in the Reserva Particular do Patrimônio Natural of the Clube Caça e Pesca Itororó de Uberlândia (CCPIU), Uberlândia, MG. Samplings were made in each 15 days on the surface of water through the "Instant Collector" of Pinese, in the year of 2006. All individuals were identified and quantified and cluster and canonical correlation data analyses were applied, as well as diversity, equitability and similarity indices. The species richness of zooplankton in the CCPIU lagoons was represented by 75 species, of which 12 genera, 29 species and one subspecie are new records for the State of Minas Gerais. The rotifer were the predominant group (75% of total species) and the Lecanidae was the most diverse family. Among cladocerans, Chydoridae highlighted themselves in richness, but not in abundance, since this emphasis was given to Bosminidae family. Too few adults of copepods were founded, but nauplii were fairly frequent; Cyclopidae was the largest family of occurrence among this group but there was no record of any individuals of Calanoida order. There was a great difference between the biologic composition of the two lakes studied. The aquatic macrophytes present in one of the ponds were responsible for a great diversity of zooplanktonic species in this environment, but on the other hand provided a decline in this animal s biomass due to the imprisonment of minerals available in the system on the perennial vegetal biomass. The lake without macrophytes showed a buoyant planktonic density, since in this system, in the absence of aquatic macrophytes, the entire water fertility was directed to the phytoplankton, but the low variety of habitat resulted in a reduced number of species of this environment. Many studies concerning zooplankton must be developed in communities of veredas in Brazil, in order to understand the complex ecological standards, and biological diversity and swing them as a flag to the conservation of the aquatic ecosystems.